The Effect of Social Media Agility on Sme Performance in Indonesia: The Moderating Role of Digital Literacy and Environmental Dynamism - Jennifer Wibisono; Charly Hongdiyanto (Journal of Social Research, 2026)
This study examines the effect of social media agility on the performance of small and medium-sized enterprises (SMEs) in Indonesia, with digital literacy and environmental dynamism serving as moderating variables. In an increasingly dynamic digital business environment, SMEs are required to respond quickly and flexibly to market changes, customer interactions, and competitive pressures through the effective use of social media. This research adopts a quantitative approach using a survey method, with data collected from SME owners and managers across various sectors in Indonesia. The data were analyzed using structural equation modeling to assess the direct and moderating relationships among variables. The findings indicate that social media agility has a significant positive effect on SME performance. Furthermore, digital literacy strengthens the relationship between social media agility and SME performance, suggesting that SMEs with higher levels of digital literacy are better able to leverage social media agility to enhance business outcomes. Environmental dynamism is also found to moderate this relationship, wherein higher levels of environmental uncertainty amplify the importance of social media agility in improving SME performance. These results highlight the critical role of social media agility as a strategic capability for SMEs, particularly when supported by adequate digital literacy and adaptability to dynamic environmental conditions. The study contributes to the literature on digital transformation and SME performance by providing empirical evidence from an emerging economy context.